Preferences and Behaviour Toward E-Gadgets : A Study of Consumers in Chandigarh - Savita, Ubba; Sheoran, Upasana (Indian Journal of Marketing, 2020)
The evolution of recent electronic gadgets in the current era has grabbed the attention of global population. The Indian customers have also got lured towards these innovative products. The objective of the study was to explore and understand the behavioural aspects of Indian customers towards e-gadgets. The data were collected from 100 respondents with the help of a structured questionnaire from the Union Territory of Chandigarh in India. Frequency and percentage were used to process the information provided by the respondents. Friedman rank test was also applied to calculate the mean rank of the ordinal scaled questions. The popular e-gadgets among the respondents were found to be mobile phones and laptops. Fitbit/smart watches and smart speakers were the new entrants into few respondents’ kitty. Specifications of the gadgets and latest technology were the top attributes that the respondents looked for. The preferred sources of information about latest trends in e-gadgets were social media and word of mouth. Cash and debit cards were the preferred mode of payment for these gadgets.